The Effect of The Application of Head Coaching on The Work Motivation and Job Satisfaction of The Implementing Nurse at The Bandar Lampung Advent Hospital - Magdalena Gulo; Sutanto Priyo Hastono; Catharina Dwiana Wijayanti (Al Makki Publisher, 2025)
Nursing human resources today are experiencing a change in the generation of workers. The need for the role of the head nurse in carrying out coaching to support, collaborate, and facilitate nursing human resources of different generations in order to build effective working relationships, increase motivation, self-potential, and staff job satisfaction. The purpose of the study was to assess the impact of coaching training on nurses' motivation and job satisfaction. Quasi-experimental research design with one group pre-posttest design. Respondents in the research were implementing nurses, using questionnaire measuring tools. The results were obtained by the majority of respondents aged 20-30 years (42.9%), PK 2 career path (37.5%), nurse education (50.0%), and length of work 1-5 years (44.6%). Before the coaching training, the average motivation was 25.13 and job satisfaction was 23.73, while after the coaching training, the average motivation increased to 43 and job satisfaction increased to 35.98. The Paired Samples Test showed a significant effect of coaching training on motivation and job satisfaction with a p-value of 0.000, as well as an R square result of 0.838. The need for the implementation of coaching by the head of the room to increase the motivation and work of nurses which will have an impact on the quality and effectiveness of nursing services.